Work content of in-house translators in small and medium-sized industrial enterprises. Observing real work situations - Kuźnik, Anna (2016)
This paper focuses on the impact of the organisational context on the translation activity of in-house translators working in small and medium-sized industrial enterprises. The aim is to answer the question of what the work content of in-house translators is when it is embedded in the whole industrial work process. The paper includes an introductory section that outlines the conceptual background of the sociology of work. The involvement of the translator as a central agent in the execution of the wider work process is analysed in a case study, based on data gathered in 2005 and 2006 using observational methods in a medium-sized Polish company producing ice cream machines. The results obtained are linked with those from other research projects carried out in Translation Studies. The paper concludes with the statement that the more complete the translator’s view of the work process is, the better his understanding of his own activity is and therefore the greater his efficiency is.
Keywords: work content; work process; lean production; small and medium-sized enterprises; translation; in-house translator